TRANSFORMATION OF THE HUMAN PROSTATE GLAND IN INTERMEDIATE AND LATE FETAL PERIODS OF DEVELOPMENT - Irina Piatsko; Alexander Usovich (Asociación Argentina de Anatomía Clínica, 2020)
The purpose of the study was to determinate the morphometric parameters of epithelial cords, prostatic ducts, acini of the human prostate gland and their lining epithelium, the shape of prostate glands, and muscle tissue in fetal periods of development. Material and Method: The study was performed on 19 prostate glands of male sex fetuses of intermediate and late fetal periods. We used the morphometric method of verification of apoptotic cells on stained histoligical preps using the criteria of apoptosis. Morphometric research included measurements of acini and acinar lumen areas, epithelium height, assessment of shape factors. Results: In the late fetal period compared to the intermediate fetal period the acini area was not increased in 1.1 times (p =0,004), the area of acinar lumens increases by 3.8 times (p=0.0005). Changes in the shape of acinar lumens were detected. Conclusion: An insignificant increase of the specific area of the glandular parenchyma in the organ of transformation of the developing glands occurs mainly due to their canalization. The formation of prostatic ducts was not followed by the increase in their total area and was the result of differentiation epithelial cells and apoptosis. Transformation of prostate glands in the prenatal period occurs in a certain sequence: the formation of epithelial buds, their canalization by apoptosis with formation of epithelial ducts and prostatic ducts, and formation of end pieces of prostate glands from these ducts. Apoptotic bodies were removed from the lumen of the prostatic ducts by extrusion. The design and orientation of the smooth muscle bundles around prostatic ducts and acini do not ensure the evacuation of content of the prostate glands in the fetal period.